Leadership Styles, Interactional Justice and Employee Well-being: A Study in Export Processing Zones of Pakistan - Tariq, Amina; Khurram, Shahzad; Ashraf, Nyela (Annals of Human and Social Sciences, 2023)
Leadership styles are considered as one the most significant component of overall organization configuration. While employee wellbeing and its connection with the overall organization’s configuration is necessary to examine, it is equally important to include leadership styles in the research perspective. For this purpose, we conducted a study in which we include main types of religious leadership’s styles and regressed them against employees’ wellbeing. For this quantitative study, data was gathered through questionnaires given to total 511 employees who are working in various export processing zones of Pakistan. In this study, we also examined the mediating effects of interactional justice on religious leadership styles to well-being relationships. We found that religious leadership styles have strong and positive impact on employee well-being and the mediation effect also exists in these relationships.